Laparoscopic versus Open appendectomy in Acute Appendicitis - Batajoo, H; Hazra, N K (Journal of Nepal Health Research Council, 2013)
Background: Although laparoscopic appendectomy is widely practiced nowadays, controversy still continues about the advantages of laparoscopic versus open appendectomy. To compare LA with OA to determine the length of hospital stay, post operative morbidity and length of operation. Methods: A retrospective study carried out, between February 2009 and January 2012, involving 226 patients (111 males and 115 females) with a diagnosis of suspected acute appendicitis. LA group consisted of 54 patients and OA group of 172 patients. The groups were compared by using Chi-square test for categorical variables and student t-test for continuous variables. Results: The mean length of hospital stay in LA was 2.69 days and in OA 4.03days (p